FACTORS RELATED TO COMPLETE BASIC IMMUNIZATION BEHAVIOR IN THE WORKING AREA OF THE TALANG ULU HEALTH CENTER - Novega Novega; Tenike Gita Miranda; Amin Kurnia; Fourni Ardiansyah (Proceeding B-ICON, 2022)
The immunization coverage program is a program to improve public health in order to achieve the vision of an independent community for healthy living, one of the targets is to reduce infant mortality. Data on the number of UCI villages in the Talang Ulu Health Center is 71.4% of the 7 villages. This research was to determine the relationship between knowledge and the role of health workers with complete basic immunization behaviors. This research used a cross-sectional approach. The research sample was mothers who had children aged 10-12 months as many as 71 people. Samples were selected using a simple random sampling technique. The data was collected through interviews using questionnaires. The data that had been collected were analyzed univariately and bivariately with statistical tests of the Chi square test. Univariate results showed that 71.8% of respondents had incomplete basic immunization behaviors, 62% had poor knowledge and 71.8% stated that the role of health workers was not good. Bivariate results showed that there was a relationship between knowledge (p=0.034) and the role of health workers (p=0.000) with complete basic immunization behavior in the working area of the Talang Ulu Health Center in 2021. Variables related to complete basic immunization behavior were the knowledge and role of health workers. We recommend increasing the role as an educator through counseling or counseling activities about immunizations given when mothers visit health care places, so as to increase maternal knowledge about the importance of immunization in infants.